Sociodemographic characterization of patients diagnosed with gastric cancer in a Hospital in Huanuco, 2017-2019 - Morales-Canteño, Fresia (2020)
Objective. To characterize sociodemographically patients diagnosed with gastric cancer at a hospital in Huánuco during the period between 2017 and 2019. Methods. An observational and descriptive study was carried out. Retrospective dataw was used by reviewing the medical records of 70 patients diagnosed with gastric cancer at Hospial Regional Hermilio Valdizán de Huánuco between 2017 and 2019. Frequency analysis was used to data analysis. Results. From the total number of patients diagnosed with gastric cancer, 34.3 % of cases corresponded to 2017, 45.7 % to 2018 and 20 % to 2019. Regarding the demographic characteristics of patients diagnosed with gastric cancer, 71 4% were seniors. 71.4 % of the population was male and 64.3 % came from a rural area. Regarding social characteristics, 74.3 % of the population only had primary studies. Conclusion. When characterizing sociodemographically, it was obtained that the male gender has a higherfrequency of diagnosis of gastric cancer, as well as seniors.